1994
DOI: 10.1007/bf01476493
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 20 primarily surgically treated chiasmatic/hypothalamic pilocytic astrocytomas

Abstract: The authors review the therapeutic results of 20 patients (aged 12 months to 30 years, mean age 9 years) with benign pilocytic astrocytoma of the chiasmatic/hypothalamic region, seen at the University Hospital Hamburg-Eppendorf between February 1980 and April 1993. Six patients suffered from neurofibromatosis 1 (NF-1). The patients were divided into two subgroups relative to tumour extension and growth patterns, as revealed by CT scans and/or MR imaging. Fourteen patients revealed a large globular suprasellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Astrocytomas of the optic chiasm and hypothalamus make up 10 % to 15 % of supratentorial tumours in children; males and females are approximately equally affected. One-third of patients have neurofibromatosis type 1 (NF1) [37]. …”
Section: Supratentorial Manifestationsmentioning
confidence: 99%
“…Astrocytomas of the optic chiasm and hypothalamus make up 10 % to 15 % of supratentorial tumours in children; males and females are approximately equally affected. One-third of patients have neurofibromatosis type 1 (NF1) [37]. …”
Section: Supratentorial Manifestationsmentioning
confidence: 99%
“…Studies have shown NF to have a protective effect [13. 19,20], no effect [6], and a deleterious effect [21] on the prognosis of patients with chiasmal astrocytomas. We found no rela tionship between outcome and NF.…”
Section: Discussionmentioning
confidence: 99%
“…On CT, the hypothalamic-chiasmatic astrocytoma mass is hypointense or isointense with enhancement. 96,97 On MR imaging, a hypothalamic-chiasmatic astrocytoma has classically T2WI hyperintense and T1WI hypointense to isointense signal and mild to avid enhancement. 90 There is usually …”
Section: Hypothalamic-chiasmatic Gliomamentioning
confidence: 99%